Uncertainty of Regulation in the Fight against Extremism in International and National Law - I. A. Orlova; Yu. V. Mishalchenko; M. Pacek (Управленческое консультирование)
The article analyzes the concept of “extremism” in national and international law, examines the problem of criminalization of extremism in the legislation of the Russian Federation, foreign states and international legal acts, identifes lacunas and contradictions in the legal regulation of relations aimed at countering extremism, it is argued that legal certainty is one of the factors of the eﬀectiveness of international cooperation in the fght against extremism and terrorism.